St. Vincent and the Grenadines : Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that growth in St. Vincent and the Grenadines in 2017 is expected to remain relatively flat. The current account deficit is expected to narrow reflecting additional profit repatriation by telecommunication companies. The domestic banking system remains stable, but credit to the private sector has been flat. The fiscal situation is projected to worsen substantially in 2017 owing to a projected decline in tax revenue after exceptional receipts in 2016 and higher outlays for transfers, subsidies and public investment. Growth is expected to pick up to 2.1 percent in 2018 and reach its potential over the medium-term.